Handbook of decision making - Morçöl, Göktuğ (Public administration and policy policy, 2007)
Identifies common patterns and the variations that different contexts may generate. This work covers the mainstream methods of decision making such as cost-benefit analysis, linear programming and queuing. It also explains alternative and emerging methods such as geographic information systems, Q-methodology and narrative policy analysis.